Enriched Environmental Conditions Modify the Gut Microbiome Composition and Fecal Markers of Inflammation in Parkinson’s Disease - Singh, Yogesh; El-Hadidi, Mohamed; Admard, Jakob; Wassouf, Zinah; Schulze-Hentrich, Julia M.; Kohlhofer, Ursula; Quintanilla-Martinez, Leticia; Huson, Daniel; Riess, Olaf; Casadei, Nicolas (Frontiers in Neuroscience, 2019)
Recent findings suggest an implication of the gut microbiome in Parkinson’s disease (PD) patients. PD onset and progression has also been linked with various environmental factors such as physical activity, exposure to pesticides, head injury, nicotine, and dietary factors. In this study, we used a mouse model overexpressing the complete human SNCA genes (SNCA-TG mice) modeling familial and sporadic forms of PD to study whether environmental conditions such as standard versus enriched environment changes the gut microbiome and influences disease progression. We performed 16S rRNA DNA sequencing on fecal samples for microbiome analysis and studied fecal inflammatory calprotectin from the colon of control and SNCA-TG mice kept under standard environment (SE) and enriched environment (EE) conditions. The overall composition of the gut microbiota was not changed in SNCA-TG mice compared with WT in EE with respect to SE, however, individual gut bacteria at genus level such as Lactobacillus sp. were significantly changed in SNCA-TG mice. EE significantly reduced colon fecal inflammatory calprotectin protein in WT and SNCA-TG EE compared to SE. Moreover, EE reduces the pro-inflammatory cytokines in the feces and inflammation inducing genes in the colon. Our data suggest that an enriched social environment has a positive effect on the induction of SNCA mediated inflammation in the intestine and by modulating anti-inflammatory gut bacteria.